Spatial factors as contextual qualifiers of information seeking - R. Savolainen (Information Research: An International Electronic Journal)
Introduction. This paper investigates the ways in which spatial factors have been approached in information seeking studies. The main attention was focused on studies discussing information seeking on the level of source selection and use. Method. Conceptual analysis of about 100 articles and books thematizing spatial issues of information seeking. Due to research economy, the main attention was paid to studies on everyday life information seeking. Results. Three major viewpoints were identified with regard to the degree of objectivity of spatial factors. The objectifying approach conceives of spatial factors as external and entity-like qualifiers that primarly constrain information seeking. The realistic-pragmatic approach emphasizes the ways in which the availabilty of information sources in different places such as daily work environments orient information seeking. The perspectivist approach focuses on how people subjectively assess the significance of various sources by means of spatial constructs such as information horizons. Conclusion. Spatial factors are centrally important contextual qualifiers of information seeking. There is a need to further explore the potential of the above viewpoints by relating the spatial and temporal factors of information seeking.